The application of incisional negative pressure wound therapy for perineal wounds: A systematic review. Issue 5 (4th June 2018) - Cahill, Caitlin; Fowler, Amanda; Williams, Lara J
Abstract : Impaired perineal wound healing is a major source of morbidity after abdominoperineal resection. Incisional negative pressure wound therapy can improve healing, prevent infections, and decrease the frequency of dehiscence. Our objective was to summarise existing evidence on the use of incisional negative pressure wound therapy on perineal wounds after abdominoperineal resection and to determine the effect on perineal wound complications. Electronic databases were searched in January 2017. Studies describing the use of incisional negative pressure wound therapy on primarily closed perineal wounds after abdominoperineal resection were included. Of the 278 identified articles, 5 were retrieved for inclusion in the systematic review ( n  = 169 patients). A significant decrease in perineal wound complications when using incisional negative pressure wound therapy was demonstrated, with surgical site infection rates as low as 9% (vs 41% in control groups). The major limitation of this systematic review was a small number of retrieved studies with small patient populations, high heterogeneity, and methodological issues. This review suggests that incisional negative pressure wound therapy decreases perineal wound complications after abdominoperineal resection. Further prospective trials with larger patient populations would be needed to confirm this association and delineate which patients might benefit most from the intervention.